Penggunaan multimedia interaktif untuk meningkatkan literasi digital siswa SMP pada mata pelajaran IPA - Muhammad Aqmal Nurcahyo (Jurnal Pendidikan Informatika dan Sains, 2020)
This research using interactive multimedia to improve digital literacy of Junior High School students in natural science learning, focused in the material structure of the earth and disasters. The study consisted of two meetings using innovative technology in the form of interactive multimedia with different sub-material, namely (1) earth and volcanic structures, and (2) earth natural disasters and disaster mitigation. The aspects of digital literacy will be assessed in this research such as: accessing, analyzing and evaluating, creating, reflecting, and communicating. This research is qualitative research with descriptive method. Samples were taken with simple random sampling technique. Samples were student of grade VIII in 2 Junior High School in Bandung as many as 30 students. The result showed that natural science learning on the material structure of the earth and disasters by using interactive multimedia can improve digital literacy of Junior High School students with a difference overall percentage of 4.00 % from 1st meeting (70.33 %) to 2nd meeting (74.33 %). Thus, it can be concluded that by using interactive multimedia can improve digital literacy of Junior High School students in the material structure of the earth and disasters. At the end, it is expected to do a similar study related to the effort to improve digital literacy with other material.